2016
DOI: 10.1016/j.jspd.2016.01.001
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Recovery Pathway for Adolescent Idiopathic Scoliosis That Improves Pain Control and Reduces Time to Inpatient Recovery After Posterior Spinal Fusion

Abstract: Implementation of standardized RRP resulted in reduced pain, faster mobilization, reduced frequency of opioid-related side-effects, and earlier discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(93 citation statements)
references
References 38 publications
4
84
0
4
Order By: Relevance
“…Preoperative gabapentin administration has been studied in a randomized controlled trial19 and as part of a rapid recovery pathway (RRP) for spinal fusion 20. Mayell et al 19 demonstrated that patients who received a single preoperative dose of gabapentin did not show significant improvement in opioid consumption or pain scores in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative gabapentin administration has been studied in a randomized controlled trial19 and as part of a rapid recovery pathway (RRP) for spinal fusion 20. Mayell et al 19 demonstrated that patients who received a single preoperative dose of gabapentin did not show significant improvement in opioid consumption or pain scores in this population.…”
Section: Discussionmentioning
confidence: 99%
“…One additional study, was not picked up by the search but was known to the lead author, and highly relevant, and so was added to the review. 32 Of the five pertinent articles, one described the implementation of ERAS to a whole elective spinal surgery service, 32 two papers examined idiopathic scoliosis surgery, 33,34 one looked at lumbar spinal fusion, 35 and one described a series of lumbar and cervical spinal decompression patients. 36 The paper examining the adoption of ERAS to a whole elective spinal service was based in the UK, and had the hospital had organisational experience of adopting ERAS to hip and knee replacement patients.…”
Section: The Application Of Eras To Spine Surgerymentioning
confidence: 99%
“…The two studies looking at the implementation of ERAS for adolescent idiopathic scoliosis surgery, also indicated that ERAS can be successfully introduced to this pathway, and that LOS can be reduced to 3-4 days. 33,34 In one study mean length of stay was reduced by 1.7 days to 4 days after the rapid recovery pathway was fully introduced for 84 patients. 34 In this paper, the authors present the details and results of a systematic quality improvement journey, with clear details of the historical pathway, the transition period, and the implementation of ERAS.…”
Section: The Application Of Eras To Spine Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Its analgesic efficacy is similar to that of morphine, and it can help reduce the incidence of opioid-associated postoperative nausea and vomiting. 53 Other options for intravenous nonopiate analgesia include low-dose ketamine infusions, intermittent diazepam, 54,55 and butorphanol 56 injections.…”
Section: Surgical Site Infectionmentioning
confidence: 99%